Significance of nanotechnology in medical sciences - Gaur, Ajay; Midha1, Anil; Bhatia, Arvind L (Asian Journal of Pharmaceutics (AJP), 2014)
Nanotechnology refers broadly to a field of applied science and technology whose unifying theme is the control of matter on the molecular level in scales smaller than 1 Î¼m, normally 1-100 nm, and the fabrication of devices within that size range. Two main approaches are used in nanotechnology. In the â€œbottom-upâ€ approach, materials and devices are built from molecular components, which assemble themselves chemically by principles of molecular recognition. In the â€œtop-downâ€ approach, nano-objects are constructed from larger entities without atomic-level control. In addition, as the need for the development of new medicines is pressing, and given the inherent nanoscale functions of the biological components of living cells, nanotechnology has been applied to diverse medical fields such as oncology, cardiovascular medicine, and in treatment of other chronic diseases. Indeed, nanotechnology is being used to refine discovery of biomarkers, molecular diagnostics, and drug discovery and drug delivery, which could be applicable to management of these patients. In this review, we will focus upon significance of nanotechnology in medical sciences, as well as the plausible side effects related to their use.